2014
DOI: 10.1038/mi.2014.6
|View full text |Cite
|
Sign up to set email alerts
|

An airway epithelial iNOS–DUOX2–thyroid peroxidase metabolome drives Th1/Th2 nitrative stress in human severe asthma

Abstract: Severe refractory asthma is associated with enhanced nitrative stress. To determine the mechanisms for high nitrative stress in human severe asthma, 3-nitrotyrosine (3NT) was compared with Th1 and Th2 cytokine expression. In severe asthma, high 3NT levels were associated with high IFN-γ and low IL-13 expression, both of which have been reported to increase inducible nitric oxide synthase (iNOS) in human airway epithelial cells (HAEC). We found IL-13 and IFN-γ synergistically enhanced iNOS, nitrite and 3NT, cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
107
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 52 publications
7
107
0
1
Order By: Relevance
“…This focuses our attention on other effector functions of the T cell cytokines in asthma pathophysiology. We have recently shown synergistic interactions between IFN-γ and low levels of IL-13 in induction of nitro-oxidative stress in primary airway epithelial cells (33). Despite the use of high doses of oral CS, IL-13 was still detectable at low levels in the BAL cell culture supernatants of SA subjects in our study ( Figure 1C).…”
Section: Discussionmentioning
confidence: 56%
“…This focuses our attention on other effector functions of the T cell cytokines in asthma pathophysiology. We have recently shown synergistic interactions between IFN-γ and low levels of IL-13 in induction of nitro-oxidative stress in primary airway epithelial cells (33). Despite the use of high doses of oral CS, IL-13 was still detectable at low levels in the BAL cell culture supernatants of SA subjects in our study ( Figure 1C).…”
Section: Discussionmentioning
confidence: 56%
“…IL-13 and IFN-γ synergistically enhanced iNOS activation and production of nitrite and 3 nitro-tyrosine (3NT) in epithelial cells, which correlated with increased H 2 O 2 production (114). This in vitro effect on oxidative stress in the epithelial cells closely corresponded to high levels of 3NT and IFNG mRNA in the lungs of severe asthma subjects (114). Figure 2 illustrates our current understanding of altered immune responses in the nasal tissue and airways that underlie severe asthma.…”
Section: Downstream Effects Of Ifn-γ Influencing the Severe Asthma Phmentioning
confidence: 99%
“…Thus, it is possible that SLPI plays a fundamental role in inhibiting both allergen-and cell-associated proteases such that SLPI downregulation promotes a severe asthma phenotype via effects on AHR, FeNO levels, and airway remodeling. IFN-γ also synergizes with type 2 cytokines such as IL-13 to promote nitro-oxidative stress in airway epithelial cells (114). IL-13 and IFN-γ synergistically enhanced iNOS activation and production of nitrite and 3 nitro-tyrosine (3NT) in epithelial cells, which correlated with increased H 2 O 2 production (114).…”
Section: Downstream Effects Of Ifn-γ Influencing the Severe Asthma Phmentioning
confidence: 99%
See 1 more Smart Citation
“…These ROS can react with the 'constitutively' produced NO, leading to the observed unchanged 3-nitrotyrosine (3-NT) levels in patients with asthma [30]. Indeed, an in vitro study using human alveolar epithelial cells of patients with severe asthma, has shown that not only nitrite, produced by iNOS, but also H 2 O 2 , produced by dual oxidases, are important in the formation of 3-NT [51].…”
Section: Inducible No Synthase Inhibitorsmentioning
confidence: 99%